Inserção de fornecedores locais como fonte de desempenhos em custos de transação e legitimidade: estudo de caso na cadeia produtiva do petróleo e gás do Rio Grande do Norte - Costa, Antônio Rufino da (2009)
The inclusion of local suppliers in production chains has considerable impact on its performance, but most notably in its main actors. The results of this process may be of different kinds and can be analyzed from economic or institutional approaches. This study aimed to verify the existence of different performances of Petrobras due to the inclusion of local suppliers in the oil and gas production chain in the state of Rio Grande do Norte, from the viewpoints of transaction costs and the Institutional Theory. In order to this, were made the characterization of the PROMINP, the description of its actions and results, the mapping of its institutional context of reference, and identification of results obtained by Petrobras in terms of transaction costs and legitimacy. The theoretical framework is based on authors dealing with industrial concentration, as like Marshall, Krugman, Porter and Schmitz, from the sociological perspective of neoinstitucional theory, as like DiMaggio and Powell and Scott and Meyer, and transaction costs, as like Williamson. This is a qualitative research, with data collection done by consulting secondary fonts and semi-structured interviews with nineteen actors of three groups, namely: actors involved in actions of the program, representatives of enterprises and representative of Petrobras. To analyze the content was used the Suchman s model (1995) for categories associated with strategies of legitimation and fourteen variables associated with the three variables assets specificity, bounded rationality and opportunism (Williamson, 1995, 1989) in the case of transaction costs. The results indicate that PROMINP has achieved its objectives by encouraging the increased participation of local companies in the oil and gas production chain, reflecting in the economic development of the state. The Redepetro/RN, fostered and built upon the interaction of the participants, is presented as a solution of continuity to the participation of enterprises in the chain, after the closure of the actions of the program. PROMINP demands responses to coercive, legislative and regulatory pressures of the organizational field, whose institutional context of reference is wide. From the point of view of legitimacy, through strategies to gain cognitive legitimacy and maintaining pragmatic legitimacy, Petrobras can manipulate the environment, ensuring the compliance of the constituents to their technical and institutional demands. Enterprises, in turn, respond to the demands through compliance with technical demands, mainly through the certification of processes, and cultural changes. There aren t clear gains related to the transaction costs, however, gains in legitimacy can be seen as a cumulative capital that can serve as a competitive differential that generates economic gains. In terms of theoretical findings, it was found that, due to its explanatory power for actions that are difficult to explain only in economic terms, Institutional Theory may be used as theoretical support concurrent with other theories. TCE model has limitations in explaining the program actions. In the case, it s emphasized that Petrobras doesn t seek only economic efficiency, but has in its mission the commitment to social development.